English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

if x^2 - 13x + 42 = (x + A)(x + B), then A + B =


Ohh wow.
can someone explain

this is what I started doing

x^2-13x+42=(x- )(x+ )

2007-10-23 13:23:34 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

x^2+bx+c = (x+A)(x+B)
=> A+B= b and A*B=c
=> A+B= -13

2007-10-23 13:29:12 · answer #1 · answered by namvt2000 6 · 0 0

x^2-13x+42=(x-7)(x-6), then A + B = -13

2007-10-23 20:28:30 · answer #2 · answered by JazzyJeff 2 · 0 0

A+ B= -13
Its x^-7x-6x+42= x ( x-7) -6 (x-7 )
hence ( x - 7 ) , ( x -6 )
A= -7, B= -6

2007-10-23 22:20:21 · answer #3 · answered by jai kishan 1 · 0 0

Hello,

(x -6)(x-7) So -6 + -7 = -13

Hope This Helps!

2007-10-23 20:28:33 · answer #4 · answered by CipherMan 5 · 0 0

fedest.com, questions and answers